Education Policy and Human Capital Development: Evaluating the Effectiveness of Different Education Policies in Uzbekistan - Kuziyeva Gulnoza Rashidovna (European Science Publishing, 2023)
This research article explores the critical relationship between education and human capital, highlighting their profound impact on individual and societal development. Drawing upon extensive literature review and empirical evidence, the article delves into the multifaceted dimensions of education as a driver of human capital formation and its consequent implications for sustainable growth. The study emphasizes the need for effective policies and investments in education to foster human capital accumulation, leading to enhanced productivity, innovation, and inclusive socio-economic progress. Furthermore, it underscores the role of education in addressing contemporary challenges and achieving the United Nations' Sustainable Development Goals (SDGs). The findings of this research emphasize the urgency of prioritizing education and human capital development as integral components of a comprehensive development agenda.